(untitled) (International Journal of Engineering and Computer Science, 2017)
The objective of this paper is to develop a WI-FI controlled surveillance robot using wireless Network. We are trying to develop a robot that can transfer a video captured in its camera to nearby laptop that is connect with it via wireless network. This type of robot is mainly used for security purposes like in coal mines and tunnels where human intervention is impossible. This robot can be navigated through the server system via wireless network. The purpose of this surveillance robot is to navigate and deal with multiple-angled monitoring towards the environment with inexpensive hardware and free software cost. This Robot is configured with the IR sensors to enhance its ability to detect and avoid the collision.